2017
DOI: 10.1001/jamaophthalmol.2017.0074
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen Class I Genes Associated With Stevens-Johnson Syndrome and Severe Ocular Complications Following Use of Cold Medicine in a Brazilian Population

Abstract: IMPORTANCE Describing the association with human leukocyte antigen (HLA) alleles could facilitate the understanding of increased risk factors for development of Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) in patients with severe ocular complications (SOCs). OBJECTIVE To investigate the association between HLA class I genes and cold medicine (CM)-associated SJS/TEN with SOCs. DESIGN, SETTING, AND PARTICIPANTS This case-control study was conducted between February 8, 2013, and August 29, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 36 publications
2
37
0
Order By: Relevance
“…Significant risk factors for ocular involvement in SJS include exposure to drugs such as NSAIDs and cold medications 5 , 7 . About 80% of Japanese- and 53% of Brazilian SJS/TEN with SOC patients had taken cold medicines 7 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Significant risk factors for ocular involvement in SJS include exposure to drugs such as NSAIDs and cold medications 5 , 7 . About 80% of Japanese- and 53% of Brazilian SJS/TEN with SOC patients had taken cold medicines 7 9 .…”
Section: Introductionmentioning
confidence: 99%
“…However, there was no similar association found in our Korean data. Similarly, HLA-A*66:01, HLA-B*08:01 and HLA-C*12:03 were associated with CM-SJS/TEN with SOC in Brazilian population13; however, none of our subjects displayed these haplotypes suggesting that these haplotypes are rare in the Korean population. Taken together, all of these studies indicate that the association between HLA genetic variability and disease is further complicated by differences between ethnic groups and race.…”
Section: Discussionmentioning
confidence: 52%
“…The association of these HLAs with CM-SJS/TEN was confirmed by our trans-ethnic study in which Indian, Brazilian and Korean populations were included 10. HLA-A*66:01 and HLA-C*12:03 were associated with the development of CM-SJS/TEN with SOCs in the Brazilian population 13. In the Indian population, HLA-A*33:03 and HLA-C*07:01 alleles showed a significant positive association while HLA-B*57:01 and HLA-C*06:02 showed a negative association with the development of CM-SJS/TEN with SOCs 12…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…5,7,8,14,[16][17][18][19][20] We reported that 80% of our SJS/TEN with SOC patients developed SJS/TEN within several days after taking cold medicines including multi-ingredient cold medications and nonsteroidal anti-inflammatory drugs (NSAIDs) to combat the common cold. 2,5,8,20 Our Brazilian collaborators also found that more than half of their SJS/TEN with SOC patients had taken cold medicines, 21 suggesting that such medicines are major causative drugs for SJS/TEN with SOC. Our Thailand collaborators also reported that cold medicines are main causative drugs for SJS/TEN with severe chronic ocular complications: 49 of 71 patients with SJS/TEN with SOC (69%) had a history of taking CM before the onset of SJS/TEN in Thailand.…”
Section: Cold Medicine and Hla Analysismentioning
confidence: 88%